Functional and genetic characterization of dengue virus methyltransferase. - Chung, Ka Yan. (2013)
Dengue virus (DENV) is a member of the genus Flavivirus within the family Flaviviridae. DENV consists of four distinct serotypes (DENV 1-4) and causes diseases ranging from self-limiting dengue fever to life threatening dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Dengue fever is the most frequent arthropod transmitted infectious disease in humans and is endemic in the tropics and subtropics regions. Currently there is no antiviral therapy or vaccine available for treatment of DENV infections, thus causing significant human mortality and morbidity in epidemic areas. DENV is an envelope virus with a single-stranded positive-sense RNA genome approximately 11 kb in length (reviewed in Chambers et al., 1990). The open reading frame encodes a polyprotein that is post- and co-translationally cleaved by viral and cellular proteases into three structural proteins (capsid, pre-membrane and envelope) and seven non-structural (NS) proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B and NS5) (reviewed in Chambers et al., 1990). The N- and C-terminal regions of NS5 encode methyltransferase (MTase) and RNA-dependent RNA polymerase (RdRp) respectively.